Гистопатологические изменения пищеварительной железы пресноводных брюхоногих моллюсков (Gastropoda) как результат инвазии их личинками трематод - Стадниченко, А.П. (Вестник зоологии, 1968)
The author investigated histopathological changes of digestive gland in freshwater gastropoda evoked parasitizing of trematoda larvae in it. Intertubular connective tissue, being a localization point for parasites is slide apart, squeezed and destroyed as the parasites grow. The pressure exerted on tissues by trematoda larvae evoked the degenerative changes in the cells of liver tubes. The activity of histolytic substances excreted by parasites, promotes the cell necrosis.